The impact of minimum wages to the company of FELDA at Bera, Pahang / Mohd Faizol Kamarazaman - Kamarazaman, Mohd Faizol (Faculty of Plantation and Agrotechnology, 2017)
Minimum Wages Act 1948 that has been addressed in National Wages Consultative Council (NWCC) is to give a better salary and a better living cost to all the workers. Meanwhile in Malaysia, since July 2016 the rate of minimum wages increased up to RM1000 per month exclude the domestic services. The aim of this study is to investigate the biggest impact of increasing the minimum wages and workers’ productivity as well as to find out the biggest impact of the increasing the minimum wages to the employment. A survey was conducted on a company under FELDA Corporation at Bera Pahang. The data was analysed by using SPSS. The result indicated that there is a significant different between all impact since the P value is 0.024 less than 0.05. Besides, through regression shows that the biggest impact of increasing minimum wages are skill of workers at 0.053 and less impact are time management at -0.057.